Impact of Worker Remittances on Economic Growth of Pakistan: Analysis of Pakistan’s Economy - M. Mobeen Shafqat (İşletme Araştırmaları Dergisi, 2014)
We make this study for the purpose of getting logical answer about avery famous matter regarding contribution of worker’s remittance in the growth of the economy of Pakistan. We also include different variables to evaluate the exact effect of foreign exchange earnings in economic growth of Pakistan by using time series data for the duration of 1991 to 2010. Here we applied OLS multiple regressions model and also check the assumptions of OLS by different diagnostic tests. The empirical and quantitative results describe that foreign remittance are the famous mean of economic growth and have significant positive relationship with each other. The productive use of this paper can help the economy of Pakistan to maintain and improve the economic growth by investing this money into different long term and short term projects. Pakistan’s Government should provide different incentives and lower down the cost of transactions to attract the overseas Pakistani emigrants that sent money through unofficial ways.